Experimental characterization of a five blade tubular propeller turbine for pipe inline installation - Samora, Irene; Hasmatuchi, Vlad; Münch-Alligné, Cécile; Franca, Mário J.; Schleiss, Anton J.; Ramos, Helena M. (Renewable energy, 2016)
The interest in micro-hydropower in existing infrastructure is increasing since this is a technology with low environmental impacts and potential for energy recovery in different types of installation. The technologies available for these schemes are still restricted and it is a current subject for research. In this work an experimental characterization of an inline tubular propeller suitable for pressurized systems, such as water supply and distribution networks, is presented. In the framework of the European Project HYLOW, started in 2008, a first prototype has been developed using CFD analysis and tested. Nevertheless, optimization and validation were still necessary. An improved model has been now adequately tested in the laboratory and proves to be interesting in terms of potential application. The experimental investigation evidenced that the new turbine has efficiencies of around 60% for low-headed operations, below 50 m. •An 85 mm turbine was tested in an experimental facility.•The five blade tubular propeller turbine is suitable for energy recovery in water supply systems.•Measurements of flow, head and torque were carried out.•The turbine presented efficiencies of around 60%.